Practical design discovery - Brown, Daniel M. (Book Apart (Series), 2017)
Design discovery is crucial to a project's success--unite your team in an approach toward a common goal. Explore the role of discovery in product design, how to use and structure your favorite techniques for success, and how to synthesize and document what you learn. With Dan Brown's flexible framework for planning and practicing discovery activities, you'll set every design endeavor on the right path.